2015
DOI: 10.1039/c4gc01612b
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalyzed algal biomass pretreatment for integrated lipid and carbohydrate-based biofuels production

Abstract: One of the major challenges associated with algal biofuels production in a biorefinery-type setting is improving biomass utilization in its entirety, increasing the process energetic yields and providing economically viable and scalable co-product concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(142 citation statements)
references
References 52 publications
5
136
0
1
Order By: Relevance
“…It was produced from carbohydrate rich S. acutus (SCE 0401) biomass that was pretreated with dilute sulfuric acid (2% w/w) in a Jaygo reactor [130 L (Union, NJ)] at 150°C for 0.5 h to lyse cells and hydrolyze portions of the biomass. Lipids were separated from the resulting sample slurry by centrifugation, and the saccharified liquid supernatant was fermented using Saccharomyces cerevisiae (D5A) to produce ethanol after supplementation with 5 g/L yeast extract and 10 g/L peptone to the fermenter (Laurens et al, 2014). The resulting fermentation broth was assessed for nitrogen content (see below), and added to BG11 or BG11ÀN as a potential nitrogen source for algal growth, resulting in the media BG11+SABCr or BG11ÀN+SABCr, respectively.…”
Section: Media Nitrogen Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was produced from carbohydrate rich S. acutus (SCE 0401) biomass that was pretreated with dilute sulfuric acid (2% w/w) in a Jaygo reactor [130 L (Union, NJ)] at 150°C for 0.5 h to lyse cells and hydrolyze portions of the biomass. Lipids were separated from the resulting sample slurry by centrifugation, and the saccharified liquid supernatant was fermented using Saccharomyces cerevisiae (D5A) to produce ethanol after supplementation with 5 g/L yeast extract and 10 g/L peptone to the fermenter (Laurens et al, 2014). The resulting fermentation broth was assessed for nitrogen content (see below), and added to BG11 or BG11ÀN as a potential nitrogen source for algal growth, resulting in the media BG11+SABCr or BG11ÀN+SABCr, respectively.…”
Section: Media Nitrogen Sourcesmentioning
confidence: 99%
“…A promising recent approach to algal biomass processing involves using dilute acid pretreatment to lyse algal cells and hydrolyze biomass for subsequent conversion to biofuels and/or high value products (Laurens et al, 2014;Martin et al, 2007). In this approach, algal biomass is treated with dilute sulfuric acid at moderately elevated temperatures (ca.…”
Section: Introductionmentioning
confidence: 99%
“…The protein-rich residue left after lipid extraction was converted to biogas by anaerobic digestion (AD) and this biogas was used for co-generation of heat and power on-site. While this approach is a relatively new conceptual processing pathway, early research conducted at NREL has demonstrated encouraging results with high yields (N65%) for hydrolysis of algal carbohydrates to monomeric sugars, and high yields (N80%) of fermentable sugars to ethanol as well as recovery of lipids via a wet extraction process at roughly 80 wt% moisture content [5].…”
Section: Introductionmentioning
confidence: 92%
“…Heterogeneous solid acid catalysts have also been reported for acidic hydrolysis of biomass to improve lipid extraction [174,175]. Laurens et al (2015) reported that dilute acid pretreatment can assist lipid extraction to recover up to 97% of total fatty acids using hexane. The microalgal cell wall was ruptured and degraded, allowing large oil droplets, which were entrained in the cell debris but readily extracted (Fig.…”
Section: Chemical Hydrolysismentioning
confidence: 99%